A prospective, randomized, controlled study using OsseoSpeed™ implants placed in maxillary fresh extraction socket: soft tissues response. Issue 1 (2nd December 2013) - Cecchinato, Denis; Lops, Diego; Salvi, Giovanni E.; Sanz, Mariano
Abstract Purpose The aim of this work was to study the peri‐implant soft tissues response, by evaluating both the recession and the papilla indexes, of patients treated with implants with two different configurations. In addition, data were stratified by tooth category, smoking habit and thickness of buccal bone wall. Materials and methods The clinical trial was designed as a prospective, randomized‐controlled multicenter study. Adults in need of one or more implants replacing teeth to be removed in the maxilla within the region 15–25 were recruited. Following tooth extraction, the site was randomly allocated to receive either a cylindrical or conical/cylindrical implant. The following parameters were studied: (i) Soft tissue recession (REC) measured by comparing the gingival zenith (GZ) score at baseline (permanent restoration) with that of the yearly follow‐up visits over a period of 3 years (V1, V2 and V3). (ii) Interdental Papilla Index (PI): PI measurements were performed at baseline and compared with that of the follow‐up visits. In addition, data were stratified by different variables: tooth category: anterior (incisors and canine) and posterior (first and second premolar); smoking habit: patient smoker (habitual or occasional smoker at inclusion) or non‐smoker (non‐smoker or ex‐smoker at inclusion) and thickness of buccal bone wall (TB): TB ≤ 1 mm (thin buccal wall) or TB > 1 mm (thick buccal wall). Results A total of 93 patients were treated with 93 implants. At the surgical re‐entry one implant was mobile and then removed; moreover, one patient was lost to follow‐up. Ninety‐one patients were restored with 91 implant‐supported permanent single crowns. After the 3‐year follow‐up, a mean gain of 0.23 mm of GZ was measured; moreover, 79% and 72% of mesial and distal papillae were classified as >50%/ complete, respectively. From the stratification analysis, not significant differences were found between the mean GZ scores of implants with TB ≤ 1 mm (thin buccal wall) and TB > 1 mm (thick buccal wall), respectively (P < 0.05, Mann–Whitney U‐test) at baseline, at V1, V2 and V3 follow‐up visits. Also, the other variables did not seem to influence GZ changes over the follow‐up period. Moreover, a re‐growth of the interproximal mesial and distal papillae was the general trend observed independently from the variables studied. Conclusions Immediate single implant treatment may be considered a predictable option regarding soft tissue stability over a period of 3 years of follow‐up. An overall buccal soft tissue stability was observed during the GZ changes from the baseline to the 3 years of follow‐up with a mean GZ reduction of 0.23 mm. A nearly full papillary re‐growth can be detectable over a minimum period of 2 years of follow‐up for both cylindrical and conical/cylindrical implants. Both the interproximal papilla filling and the midfacial mucosa stability were not influenced by variables such as type of fixture configuration, tooth category, smoke habit, and thickness of buccal bone wall of ≤ 1 mm (thin buccal wall).